Pengaruh Social Media Marketing, Celebrity Endorsement dan Word of Mouth terhadap Minat Beli Wear Hepi - Wardi, Putri Amalia; Ramdani, Rizal; Assa'ady, M. Chothibul Umam (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The fashion industry continues to evolve in response to the growing consumer demand for clothing that is not only functional but also reflects lifestyle trends. Wearing Hepi is a local fashion brand that offers apparel designed to follow current fashion trends. To enhance its competitiveness and attract consumer purchase interest, Wear Hepi implements various marketing strategies, including Social media marketing, Celebrity Endorsement, and Word of Mouth. This study employs an associative method with a quantitative approach. Data was collected through questionnaires distributed to 100 respondents. The results indicate that Social media marketing has a significance level of 0.072, suggesting that this strategy does not significantly influence consumer purchase intention. Celebrity Endorsement shows a significance level of 0.001, indicating a positive and significant effect on purchase intention. Meanwhile, Word of Mouth yields a significance level of 0.000, demonstrating a significant influence on consumer purchase intention.